ANTIOXIDANT ACTIVITY, TOTAL PHENOLIC CONTENT OF ESSENTIAL OILS, AND EXTRACT DETERMINED FROM NATURAL LEAVES, IN-VITRO LEAVES, AND CALLUS SOURCES OF MELALEUCA ALTERNIFOLIA – A COMPARATIVE STUDY - M, JEYAKANI; M, RAJALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Essential oil and their compounds are getting increasing interest due to their multipurpose functional as alternatives to artificial preservatives. The aim of this study was focused to comparative analyses on hydrodistillation, total phenolic content (TPC), and antioxidant activity of essential oil derived from Melaleuca alternifolia (M. alternifolia) leaves procured from natural leaves, in-vitro leaves, and callus sources. Methods: The essential oil was extracted using hydrodistillation. The Folin-Ciocalteu method was used to determine the TPC equivalent and antioxidant activity of essential oils. Results: TPC of essential oil from in-vitro sources of leaves contained 14.79 mg gallic acid equivalent/g dry plant material and its IC50 value was found to be 70% in 1-diphenyl 2-picrylhyorazyl assay. Thus, this source of essential oil showed good free radical scavenging activity. Conclusion: The estimated biological potential was obtained in the essential oil from in-vitro sources of leaves M. alternifolia.